2021
DOI: 10.1186/s12862-021-01945-z
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome as an indicator of habitat disturbance in a Critically Endangered lemur

Abstract: Background Habitat disturbance affects the biology and health of animals globally. Understanding the factors that contribute to the differential responses of animals to habitat disturbance is critical for conservation. The gut microbiota represents a potential pathway through which host responses to habitat disturbance might be mediated. However, a lack of quantitative environmental data in many gut microbiome (GM) studies of wild animals limits our ability to pinpoint mechanisms through which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 75 publications
0
6
1
Order By: Relevance
“…Our study contributes to bridging this gap by showing that degradation of the host habitat through land-use changes can indeed induce a shift in the composition of microbial communities, and even have a positive effect, on the overall bacterial species richness associated with insects. This is in clear contradiction with our original expectations that degradation of the host habitat would also be detrimental to their associated microbial diversity and functionality (McManus et al 2021, Teng et al 2022). One possible explanation for these results is that habitat degradation in the Åland meadow network is not strong enough to lead to microbial erosion in the insect species studied.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Our study contributes to bridging this gap by showing that degradation of the host habitat through land-use changes can indeed induce a shift in the composition of microbial communities, and even have a positive effect, on the overall bacterial species richness associated with insects. This is in clear contradiction with our original expectations that degradation of the host habitat would also be detrimental to their associated microbial diversity and functionality (McManus et al 2021, Teng et al 2022). One possible explanation for these results is that habitat degradation in the Åland meadow network is not strong enough to lead to microbial erosion in the insect species studied.…”
Section: Discussioncontrasting
confidence: 97%
“…For many species, the composition of the microbiota, and especially that of the gut microbiota, is representative of their diet (McManus et al 2021). Recently, Teng et al (2022) suggested that differences in the gut microbiota associated with populations from three rodent species were linked to changes in diets between populations.…”
Section: Discussionmentioning
confidence: 99%
“…Animals commonly depend on physiological regulation in case of being unable to make further adaptations by shifting behavior when facing harsh existential conditions ( Wong and Candolin, 2015 ; Bahram et al, 2016 ). Of the various physiological expressions, gut microbiota can be considered an effective indicator of the physiology and even the health status of wild animals ( McManus et al, 2021 ). The dynamic balance established between the gut microbiota and host in their long-term interactions is related to energy acquisition and nutritional metabolism ( Wu et al, 2011 ), which affects the immune system ( Matson et al, 2021 ), nervous system ( Cryan et al, 2019 ), and growth ( Groer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of beneficial gut microbiota and functional metabolism genes is linked to the health of the species, with those in worse habitats showing a decreasing trend, which indicates that these individuals have a more potential disease risk ( Amato et al, 2013 ; Barelli et al, 2015 ; Trosvik et al, 2018 ; Wasimuddin et al, 2022 ). Furthermore, the differences in the gut microbiota of animals living in different habitats are an outcome of adaptive alterations in response to ecological changes and behavioral adjustments, notably dietary composition ( Wu et al, 2011 ; McManus et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the recent accumulation of such research findings in nonhuman primates, it is becoming increasingly evident that their living environment influences and shapes the gastrointestinal microbial community [13]. For example, within the same primate species, a correlation has been observed between the diversity of dietary items and the microbial community [14][15][16][17]. Alternately, as in primate species that live in groups, it has been hypothesized that social factors may influence the establishment of the microbial community, as the horizontal transmission of the microbiota may occur via direct social interactions between individuals within the group or even indirect interaction via shared environments [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%